"The Perfect Aryan Housewife": Intersection of Extremist Violence and Violence Against Women. (March 2023) - Scaptura, Maria N.; Hayes, Brittany E.; Gruenewald, Jeff; Parkin, William S.; Protas, Michelle E.
Despite rhetoric on the association between violence against women and extremist violence, little empirical work has examined the intersection of these forms of violence. Relying on open-source data from the Extremist Crime Database, we examine how these forms of violence intersect in terms of a strained dominant masculinity. Among the 54 extremist offenders with documented histories of violence against women, extremist offenders committed familicides ( n = 23), or violence against women as a precursor to extremist violence ( n = 25). For a small minority of offenders ( n = 6), these forms of violence intersected in a form of settling scores against women and minoritized groups.